(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
The paper presents an overview of the community archives of the lombard alpine region, focusing in particular on the extant late medieval council proceedings. The research is part of the project Writing communities. Council records in the late medieval Alps (PRIN 2022). The survey sheds some light on the record-keeping tradition of many communities within a vast scenario, from Southern Swiss Alps to East Lombard Prealps. The paper adresses archival practices, registers’ material structure, authentication techniques and content organisation of the sources. It argues that council registers were not just simple collector devices, but also flexible tools for specific administrative purposes.